PEMBELAJARAN POLA RITEM UNTUK ANAK BERKEBUTUHAN KHUSUS (AUTIS) DENGAN MEDIA WARNA - Sri Mustika Aulia; Ardipal Ardipal; Yuliasma Yuliasma (SENDRATASIK UNP, 2014)
Abstrak Children with autism are a group of children initiated through symptoms such as any obstruction of cognitive, concentration, communication, social interaction and behavior. one of the therapies which is commonly used to treat autism is musical therapy. The reccuring treatment of musical therapy formed trough musical learning can improve the memory of learning. In musical learning, the student were given musical score contained musical notes to be played. The learning was innovated through colors to ease the students in remembering the sound and rhythm. Another innovation was done through using percussion music tools. The treatment of children with autism was done through monotonous instruction in order to avoid the children misunderstanding. The children with autism need to be stimulated through what they like and to be awarded of what they have done. It was proved that the learning of rhythm through colors could improve the children concentration, behavior. Beside, the emotion of children with autism was also improved. Kata kunci : Autis, ritem, partitur